مكتبة قورينا عقود من التنوير والمعرفة 1965- 2014 - أحمد امراجع نجم (Scientific Journal of University of Benghazi, 2020)
This study seeks to investigate the role of private libraries in cultural activities and publisher in the city of Benghazi. This paper aims to shed light on the experience of the " Quryna" library, and its pioneering role in this field since it was the Libya House for Publishing and Printing and then changed its name to " Quryna Library". The importance of the study comes as it highlights the pioneering role of Dar Libya (Libya House) and then Quryna in contributing to the making of Libya's national history, cultural identity, and shaping the culture of society, by supporting writers and researchers in researching Libyan culture at a time of glory when there is a comprehensive book dealing with the general history of Libya, especially after the country's independence. The method used in the study is to collect past evidence and work on arranging it, classifying and criticizing it, then presenting it in the form of documented facts, and coming out with implications and evidence. This study helps to understand the role of the Quryna Library in the national history of Libya and build the cultural identity of the community. There is no doubt that the publications of Dar Quryna formed an important cultural tributary to the national identity and the history of Libya.